Philosophical roots of empathy - Gulin, Wojciech (Studia Psychologica: Theoria et praxis, 2006)
Empathy treated as a process stays special topic of several psychological analysis. But, it was previously an object of philosophical research. Actually, some aspects of philosophical conceptualizations of empathy have also become leading in psychological studies. In the article the author describes chosen and past views of philosophers on empathy. It is a trial of getting through to philosophical sources of interpretation of empathy. In this way the continuity of philosophical and psychological studies would be kept and present psychological studies on empathy stay more understandable.